Transforming Land and Livelihood: Analysis of Agricultural Land Abandonment in the Mid Hills of Nepal - P. Paudel, Krishna; Tamang, Sujata; Shrestha, Krishna Kumar (Journal of Forest and Livelihood, 2024)
Land grabbing is often seen as a way, among many ways, to intensify agriculture for food security around the world today. However, in Nepal, a quite opposite phenomenon is taking place. Fertile agricultural lands are being abandoned at an unprecedented degree in recent years. A critical question that then arises is: How and why productive lands are being abandoned by farmers who otherwise had cultivated them for so many generations? The question is much more relevant for a country like Nepal that faces severe food insecurity. The aim of this paper is to investigate the drivers of agricultural land abandonment in the mid hills of Nepal. This study employs a mixed method approach to data collection, using household survey and key informant interview, in four mid hill districts of Nepal. The results indicate three key drivers: first, sociopolitical instability, which forced people to move out; second, reduced agricultural production, concomitant with availability of more attractive alternative opportunities; third, farming ceasing to be a viable occupation for many farmers to maintain sustainable household economy and being seen as an occupation for those who cannot do much else. Land abandonment has serious social, economic and ecological implications, particularly for the poorest of the poor. The paper concludes by highlighting some ways to address the land abandonment issue.